2010
DOI: 10.30638/eemj.2010.031
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Residential Fire Detection Using Wireless Sensor Networks

Abstract: Prompt and accurate residential fire detection is important for on-time fire extinguishing and consequently reducing damages and life losses. To detect fire sensors are needed to measure the environmental parameters and algorithms are required to decide about occurrence of fire. Recently, wireless sensor networks (WSNs) have been used for environmental monitoring and real-time event detection because of their low implementation costs and their capability of distributed sensing and processing. Although there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 0 publications
0
64
0
1
Order By: Relevance
“…However, investigation of gas sensors such as carbon monoxide (CO) demonstrated that gas sensors contribute the most to fire detection techniques [1,13,14]. Recent studies show that temperature, ionization, photoelectric, and CO sensors together make an optimal sensor set for residential fire detection [1,2,3]. Therefore, we use these four sensors to analyze residential fire data and further to detect residential fire.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, investigation of gas sensors such as carbon monoxide (CO) demonstrated that gas sensors contribute the most to fire detection techniques [1,13,14]. Recent studies show that temperature, ionization, photoelectric, and CO sensors together make an optimal sensor set for residential fire detection [1,2,3]. Therefore, we use these four sensors to analyze residential fire data and further to detect residential fire.…”
Section: Resultsmentioning
confidence: 99%
“…By looking back to the basic notions on residential fire detection, it is seen that earlier works were conducted by only one sensor type [1]. Temperature, flame detector and air-obscuration sensors are mostly used as an individual sensor for residential fire detection [1,2]. However, investigation of gas sensors such as carbon monoxide (CO) demonstrated that gas sensors contribute the most to fire detection techniques [1,13,14].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations